Relationship between loss of load expectation and reserve margin for optimal generation planning - Muhamad Zafir S.R.; Muhamad Razali N.M.; Tengku Hashim T.J. (Penerbit UTM Press, 2023)
Generation planning utilizes reliability indices as criteria to ensure adequacy in terms of total installed capacity. Reserve Margin and Loss of Load Expectation (LOLE) are the most widely-used indices in generation adequacy evaluation. Reserve Margin is a measure of available capacity over and above the capacity needed to meet normal peak demand levels. In Peninsular Malaysia, the amount of Reserve Margin has been perceived to be high. Generally, high Reserve Margin can provide high reliability. However, it acquires more generation plant, for which some of them may not be necessary. This may indicate over investment which will be reflected in the tariff structure. LOLE is a probabilistic measure which indicates the risk at which the generation capacity fails to meet the demand and its evaluation involves specific parameters such as the plant capacity and outage rate of each generating unit. Therefore, in order to have optimum generation planning and investment efficiency, it is necessary to perform a study on the practical Reserve Margin level with respect to the current LOLE requirement without endangering the overall power system reliability. This research studies the factors affecting LOLE and evaluates the relationship between Reserve Margin and LOLE under various conditions. A modified Peninsular Malaysia system is simulated using Wien Automatic System Planning (WASP -IV) to determine LOLE focusing on thermal power plants. This study concludes that peak load and forced outage rate give significant impacts to the LOLE and thus, the reliability of the system. Effort to ensure availability especially during peak load may need to be intensified. The study also establishes an inverse exponential curve for the relationship between Reserve Margin and LOLE. It is found that the outcome of the study is to enhance generation planning decision making in obtaining the optimum Reserve Margin considering the LOLE under various conditions. 2016 Penerbit UTM Press. All rights reserved.